Using the stm32f407vg microcontroller to study the amplitude-frequency characteristics of biological tissues - Semenets, V.V.; Leonidov, V.I. (Radiotekhnika, 2023)
The electrical properties of biological tissues of a plant origin are studied using the microcontroller STM32f407vg. The formulation of the problem of identifying informative signs of the viability of biological tissues when using the method of impedance measurement is given. It is shown that since currently in medical diagnostic practice there is no instrument base that would allow in an operational setting to diagnose the ability of biological tissue to self-heal after injury and damage as a result of thermal exposure, a gunshot wound or prolonged compression, the development of methods and means of instrumental diagnostics in this area of knowledge is an important modern task. The results of experimental measurements of impedance characteristics in the frequency range of 20 Hz – 2.0 MHz are presented. The frequency dependences of the stress modulus of a biological tissue of a plant origin are analyzed in its intact state, as well as after exposure of samples of a biological tissue in a freezer. A comparative analysis of the obtained frequency dependences is carried out. A significant difference between the frequency dependences of the stress modulus on a biological tissue and the frequency dependence of the stress modulus on an isotonic solution is shown. The idea was proposed that the degree of difference in the frequency distribution of the impedance module of the biological tissue from the impedance module of the isotonic solution can serve as a criterion for assessing the degree of damage to the biological tissue.